"From Fordist Worker Resistance to Post-Fordist Capitalist Hegemony?" - Wells, Don (Labour / Le Travail, 1997)
The article reviews and comments extensivley on the books "Capitalism Comes to the Backcountry: The Goodyear Invasion of Napanee," by Bryan Palmer and "Working at Inglis: The Life and Death of Canadian Factory," David Sobel and Susan Meurer.
Keywords: BOOKS -- Reviews; CAPITALISM Comes to the Backcountry: The Goodyear Invasion of Napanee (Book); MEURER, Susan; Nonfiction; PALMER, Bryan; SOBEL, David; WORKING at Inglis: The Life & Death of Canadian Factory (Book)